Teacherpreneurs : innovative teachers who lead but don't leave - Berry, Barnett; Byrd, Ann, 1961-; Wieder, Alan, 1949- (San Francisco, California : Jossey-Bass, 2013)
'We need a bold new brand of teacher leadership that will create opportunities for teachers to practice, share, and grow their knowledge and expertise. This book is about'teacherpreneurs'--highly accomplished classroom teachers who blur the lines of distinction between those who teach in schools and those who lead them. These teacherpreneurs embody the concept that teachers can teach as well as lead the transformation of teaching and learning. It's about empowering expert teachers who can buoy the image of teaching and enforce standards among their ranks while all along making sure that their colleagues as well as education policymakers and the public know what works best for students.The book follows a small group of teacherpreneurs in their first year. We join their journey toward becoming teacher leaders whose work is not defined by administrative fiat, but by their knowledge of students and drive to influence policies that allow them and their colleagues to teach more effectively. The authors trace the teacherpreneurs' steps--and their own--in the effort to determine what it means to define and execute the concept of'teacherpreneurism' in the face of tough demands and resistant organizational structures'--
Advocating for a bold brand of teacher leadership -- Defining the teacherpreneur -- Preparing for teacherpreneurism -- Making teachers and teaching visible -- Transcending teaching's past -- Cultivating teacherpreneurs for teacher-led schools -- Meeting resistance and crossing borders -- Creating what we have imagined -- Finish(ing) lessons for teacherpreneurism -- Foreseeing 2030.
Includes bibliographical references (pages 218-267) and index.
Keywords: Teaching -- United States; Educational change -- United States